Analysis of Determinants of Sustainability of Islamic Banks in Indonesia with Islamicity Financial Performance Index as an Intervening Variable - Windari Windari; Saparuddin Siregar; Nurlaila Nurlaila (Lan Tabur: JURNAL EKONOMI SYARIAH, 2026)
To investigate the determinants of sustainable Islamic banking in Indonesia by integrating financial performance, maqashid sharia (zakat and CSR), and Islamic governance, with the Islamicity Financial Performance Index (IFPI) as a mediating variable. Quantitative research using 176 quarterly observations from four Islamic commercial banks listed on the Indonesia Stock Exchange (2015–2024). Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). Financial performance, maqashid sharia, and Islamic governance positively and significantly affect IFPI, which in turn strongly impacts sustainable Islamic banking. IFPI also mediates the relationship between these variables and sustainability, highlighting that economic, social, and spiritual integration drives long-term bank sustainability. This study introduces IFPI as a mediating variable, providing a comprehensive framework that links financial performance with sharia compliance and social responsibility, offering a novel perspective in measuring Islamic banking performance. Islamic banks should strengthen the integration of financial and sharia principles by optimizing zakat, CSR, and governance mechanisms to enhance long-term sustainability. Future research may expand samples or include additional factors like digitalization or green banking to enrich findings